Determining Signs Of Micronutrient Deficiency Among School-Age Children (Eurasian Scientific Herald, 2024)
Nutrition is one of the most important factors determining the health of the population. Proper nutrition ensures the growth and development of children, helps prevent diseases, prolong life, increase efficiency and creates conditions for adequate adaptation to the environment [2,3,14]. Micronutrients are found in the human body in extremely small quantities, but nevertheless play an important role in all biochemical processes. A lack of these substances can lead to catastrophic consequences for the child’s body [6,7]. There are several types of micronutrients, each of which performs its own specific function. However, the main purpose of all components included in the groups is to protect the body from the adverse effects of the environment